Symptom burden and needs in patients with cutaneous T-cell lymphoma - a challenge for palliative care (Paliativní medicína, 2022)
Cutaneous T-cell lymphomas (CTCL) are a rare group of non-Hodgkin lymphomas. Mycosis fungoides and Sézary syndrome, the most common subtypes of CTCL, are incurable malignancies with chronic and relapsing course. CTCLs cause a high symptom burden for patients with a negative impact on quality of life. Palliative care does not seem to be sufficiently available for patients with CTCL.This review article aims to introduce readers to the physical symptoms of CTCL and their impact on psychological and social well-being of patients, their loved ones and caregivers, and to demonstrate palliative care need as an important component of interdisciplinary and multidisciplinary care in the field of CTCL.
Keywords: cutaneous T-cell lymphoma; mycosis fungoides; Sézary syndrome; palliative care